Three Faces of Shafa. Land Ownership on Trial in Ningarhar - Wamiqullah Mumtaz (Revue des Mondes Musulmans et de la Méditerranée)
A study of three districts in the Ningarhar Province – Qasimabad, Shahidano Meena, and Achin in the Shinwar District - urban, semi-urban and rural districts respectively – provides an analysis of the role of shafa (customary and Islamic religious law relating to neighboring properties) in land seizures (or ‘land grabbing’) and, by extension, in rural and urban development. In the contemporary period of rapid urbanization, the failure of the authorities and institutions charged with land management in the Jalalabad region has prompted the population to turn to informal arrangements, through shafa law and ‘land grabbing’, to resolve their conflicts. This article illustrates the contradictory implementation of the shafa neighboring-land principle by the various actors involved in processes of urbanization and urban planning.